(untitled) - Saurin B Panchal; Pankti A Panchal; Karishma D Mehta (Academia Anesthesiologica International, 2019)
Background: Peripheral nerve block holds an important place in regional anesthesia. Application of ultrasound guidance in nerve blocks had increased success rate and minimize chances of complications. Ropivacaine, newer local anesthetic with wider safety margin, is widely used now a days in peripheral nerve blocks. Aim of our study is to compare two different concentrations of ropivacaine (0.5% and 0.75%) in axillary brachial plexus block in terms of block characteristics. Subjects and Methods: A prospective randomized study was carried out in total of 60 patients, all of them given ultrasound guided axillary brachial plexus block. All patients were randomized into group A (0.5% ropivacaine,25 ml) and group B(0.75% ropivacaine, 25 ml). Succes rate, onset/ duration of sensory and motor block, duration of postoperative analgesia and complications if any were noted. Results: Both groups were comparable in terms of demographic characterics. There was no significant difference in onset and duration of sensory and motor block, duration of analgesia and patient satisfaction for both groups. Conclusion: 0.5 % ropivacaine and 0.75% ropivacaine, both are safe and effective in axillary brachial plexus block with no added advantage of 0.75 % ropivacaine over 0.5% ropivacaine.